2020
DOI: 10.3390/plants9050650
|View full text |Cite
|
Sign up to set email alerts
|

Patatin-Related Phospholipase pPLAIIIγ Involved in Osmotic and Salt Tolerance in Arabidopsis

Abstract: Patatin-related phospholipases (pPLAs) are acyl-hydrolyzing enzymes implicated in various processes, including lipid metabolism, signal transduction, plant growth and stress responses, but the function for many specific pPLAs in plants remains unknown. Here we determine the effect of patatin-related phospholipase A pPLAIIIγ on Arabidopsis response to abiotic stress. Knockout of pPLAIIIγ rendered plants more sensitive whereas overexpression of pPLAIIIγ enhanced plant tolerance to NaCl and drought in seed germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Only the phenotypic characteristics of the pPLAIIIγ (pPLAIIIγOE) in each part of organs have not yet been characterized in Arabidopsis. A T-DNA insertional mutant (SALK_088404) has been reported by the same group to have a negligible level of transcripts as determined via quantitative real-time polymerase chain reaction (qRT-PCR) [25,26]. However, in our study, the transcripts were not significantly reduced in the SALK line (Supplementary Figure S1), and an additionally analyzed line (SAIL_832_E01) showed only 35% reduced transcripts compared to the wild type (Supplementary Figure S1).…”
Section: Overexpression Of Pplaiiiγ Affects Anisotropic Cell Elongationcontrasting
confidence: 45%
“…Only the phenotypic characteristics of the pPLAIIIγ (pPLAIIIγOE) in each part of organs have not yet been characterized in Arabidopsis. A T-DNA insertional mutant (SALK_088404) has been reported by the same group to have a negligible level of transcripts as determined via quantitative real-time polymerase chain reaction (qRT-PCR) [25,26]. However, in our study, the transcripts were not significantly reduced in the SALK line (Supplementary Figure S1), and an additionally analyzed line (SAIL_832_E01) showed only 35% reduced transcripts compared to the wild type (Supplementary Figure S1).…”
Section: Overexpression Of Pplaiiiγ Affects Anisotropic Cell Elongationcontrasting
confidence: 45%
“…Around the LD regions of the lead SNP, SYN6348, 22 candidate genes were found. Among these, the gene Zm00001eb115140 , which encodes a patatin-like phospholipase protein, has previously been reported to be involved in osmotic and salt tolerance in Arabidopsis [ 35 ]. The genes Zm00001eb115320 and Zm00001eb115330 —which encode a late embryogenesis abundant (LEA) protein and a NAD-dependent epimerase/dehydratase family protein, respectively—have been reported to participate in response to abiotic stresses [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that the activation of MAPK6 causes the phosphorylation of the antiporter Na + /H + SOS1, which contributes to reducing Na + levels in plants [ 85 ]. In contrast, analysis of a pPLAIIIγa knockout mutant in Arabidopsis showed that the plants were sensitive, while overexpression improved the tolerance of the plants to saline stress [ 86 ]. Future studies should be carried out to establish whether pPLAIIIγ responds by modulating other independent pathways to SOS during osmotic stress.…”
Section: Link Between Lipid Second Messengers and Osmotic Stressmentioning
confidence: 99%